Optimalisasi Pelayanan Bimbingan Klasikal melalui Teknik Permainan Alam Manajemen Waktu Siswa SMP Negeri 8 Denpasar - Yuliastini, Ni Komang Sri; Giri, Putu Agus Semara Putra; Deliman, Selviana; Wirsiasih, Ni Komang (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2023)
The purpose of this study was to determine the improvement of students' time management through classical services with game techniques for class VII B SMP Negeri 8 Denpasar. This research method uses classroom action research. The research proceduresconsisted of planning, action, observation and reflection which were carried out in 3 cycles. The population of this study were all 132 students of class VII SMP Negeri 8 Denpasar using the purposive random sampling technique. The subjects of this study were 28 students in class VIII B of SMP Negeri 8 Denpasar. This research data collection technique uses observation and questionnaires. While the data analysis in this study used descriptive qualitative. The results of this study indicate that there is an increase in time management through optimizing classical guidance services. Improved time management can be seen from the results of observations during the action process in classical guidance activities, namely there are demands to manage study time, extracurricular activities, play time and other activities in the neighborhood. As supporting data to determine the increase in time management is through observations made by counseling teachers and subject teachers as a comparison. The result of the class is that there is an increase in the habit of asking in the learning process gradually from cycles 1, 2 and 3. In cycle 1 the frequency of asking is 40%, cycle II is 60% and in cycle III there is 80%. Thus by optimizing classical guidance services through game techniques can improve student time management.